Kryminalny rozrachunek z romantycznym mesjanizmem w "Julu" Pawła Goźlińskiego = Criminal reckoning of romantic messianism in "Jul" by Paweł Goźliński - Rawski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In his crime novel, Paweł Goźliński confronts messianism as a set of historical-philosophical stereotypes. Goźliński shows the Great Emigration as a collection of alcoholics, gamblers and people of dubious morality, thus contradicting generally accepted historical-philological narrative. Mysterious murders committed in the dark streets of the nineteenth-century Paris are a pretext to deconstruct the foundations of messianism which feature strongly in the teaching programmes of Polish schools. The author of the article, through her meticulous analysis of the Polish romantic paradigm discussed in the novel, asks important questions about its relevance.
Keywords: Goźliński, Paweł (1971- ); powieść kryminalna; literatura polska - 21 w. - tematyka